How does economic policy uncertainty affect green innovation? - Peng, Xin-Yu; Zou, Xing-Yun; Zhao, Xin-Xin; Chang, Chun-Ping (Technological and Economic Development of Economy, 2023)
This research examines the impact of economic policy uncertainty (EPU) on green innovation by using the panel fixed effects model from 2000 to 2017 for the samples of 31 provinces in China. The general conclusion is that there exists a positive link from EPU to green innovation, and that the impact of EPU varies significantly among different provinces that have diverse levels of marketization and trade openness. Specifically, provinces with higher marketization and degrees of trade openness have witnessed stronger positive effects from EPU on green innovation, whereas the correlation is rather weak in regions with low levels of those two factors. Our findings serve as a research reference for how governments may boost green innovation in the face of increasing EPU.First published online 25 November 2022